2008
DOI: 10.1902/jop.2008.070501
|View full text |Cite
|
Sign up to set email alerts
|

Association Among Rheumatoid Arthritis, Oral Hygiene, and Periodontitis

Abstract: Subjects with RA have significantly increased periodontal attachment loss compared to controls. Oral hygiene may only partially account for this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
265
4
32

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(318 citation statements)
references
References 37 publications
17
265
4
32
Order By: Relevance
“…Indeed, RA can increase the incidence and severity of PD (independently or only partially dependent) of oral hygiene status or modifying factors. [4][5][6][7]15,16,35 Accordingly, our results show that PIA increase the severity of ePD in AIRmax mice strain, whereas in AIRmin strain (resistant to PIA development), [25][26][27][28] the severity of ePD was not altered by pristane injection, showing that the development of PIA, and not the pristane injection, is involved in the modulation of ePD severity. Similarly, adjuvant-induced arthritis in rats also results in signs of periodontal destruction.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Indeed, RA can increase the incidence and severity of PD (independently or only partially dependent) of oral hygiene status or modifying factors. [4][5][6][7]15,16,35 Accordingly, our results show that PIA increase the severity of ePD in AIRmax mice strain, whereas in AIRmin strain (resistant to PIA development), [25][26][27][28] the severity of ePD was not altered by pristane injection, showing that the development of PIA, and not the pristane injection, is involved in the modulation of ePD severity. Similarly, adjuvant-induced arthritis in rats also results in signs of periodontal destruction.…”
Section: Discussionmentioning
confidence: 68%
“…[14][15][16]23 Noncausal hypothesis state that environmental or host factors could concomitantly increase susceptibility to both RA and PD. [4][5][6][7] Accordingly, our data show that AIRmin and AIRmax mice strains share the susceptibility/resistance phenotype to both PIA and ePD. [24][25][26][27][28] This finding is reinforced in the view of the absence of environmental factors potentially involved in such interaction (namely socio-economic status and tobacco smoking) 16 in the experimental models used in this study.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…T he association between autoimmune rheumatic diseases and chronic infectious periodontal disease (PD), the leading cause of tooth loss in humans, has been studied since the 1960s (1); however, it has received increasing attention lately (2)(3)(4)(5). Data from several clinical studies suggested a potential relationship between these disorders and indicated that individuals with rheumatoid arthritis (RA) are more likely to experience periodontal problems compared with healthy counterparts (2,3,(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%